Serum Omentin-1 Level as a Biomarker in Prostate Cancer - Mohammed, Ali Miqdad; Albadr, Abrar I.; Sagban, Haider Jaber (Asian Pacific Journal of Cancer Biology, 2026)
Objective: To evaluate serum omentin-1 levels in prostate cancer patients relative to healthy controls and to assess its variation between tumor stages and Gleason score categories. Methodology: This case-control research involved 176 participants (88 prostate cancer patients and 88 controls) from the National Teaching Oncology Hospital in Najaf, Iraq. Serum omentin-1 concentrations were verified by ELISA tests, and relationships with PSA, BMI were measured. ROC analysis was used to assess diagnostic efficacy. Results: Omentin-1 levels were markedly elevated in prostate cancer patients (43.4 ± 22.6 ng/mL) compared to controls (26.1 ± 6.6 ng/mL, p < 0.01). ROC analysis showed reasonable diagnostic accuracy (AUC = 0.73). Conclusion: Serum omentin-1 levels are elevated in prostate cancer, and no significant differences were observed across tumor stages or Gleason score categories, indicating that its elevation does not appear to be stage-dependent in this cohort. Further studies are needed to elucidate the mechanistic role of omentin-1 in prostate carcinogenesis, as well as its diagnostic and prognostic potential.